Penerapan Model Numbered Head Together Berbantu Gambar Ilustrasi Untuk Meningkatan Hasil Belajar Pendidikan Kewarganegaraan Siswa SD - Runita Firdayanti; Nur Fajrie; Sumarwiyah Sumarwiyah (WASIS : Jurnal Ilmiah Pendidikan, 2021)
This study aims to describe the improvement of fourth grade students' learning outcomes at SD 2 Bae on Citizenship Education (Civics) subjects through the application of the Numbered Heads Together learning model with illustrations.This research is a classroom action research that uses Kemmis and Mc Tanggart's research design which is carried out in 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The research subjects consisted of 15 students in grade IV SD 2 Bae. The independent variable in this study is the Numbered Head Together learning model assisted by illustrations, while the dependent variable is the learning outcomes of fourth grade students of SD 2 Bae. Data collection techniques in this study used observation, interviews, tests, and documentation. The data analysis technique used is quantitative data analysis which is strengthened by qualitative data.The results of classroom action research showed an increase in student learning outcomes in the cognitive domain from 71% in the first cycle to 82.33% in the second cycle. In the affective domain, it increased by a percentage of 72.67% in the first cycle to 81.83% in the second cycle. The psychomotor domain experienced an increase in the percentage from 74.33% in the first cycle to 82.5% in the second cycle. The application of the Numbered Heads Together learning model with the help of illustrations can improve Civics learning outcomes on the subject of globalization in the cognitive, affective, and psychomotor domains.